Dynamic pain connectome functional connectivity and oscillations reflect multiple sclerosis pain. Issue 11 (November 2018) - Bosma, Rachael L.; Kim, Junseok A.; Cheng, Joshua C.; Rogachov, Anton; Hemington, Kasey S.; Osborne, Natalie R.; Oh, Jiwon; Davis, Karen D.
Abstract : Abstract: Pain is a prevalent and debilitating symptom of multiple sclerosis (MS); yet, the mechanisms underlying this pain are unknown. Previous studies have found that the functional relationships between the salience network (SN), specifically the right temporoparietal junction a SN node, and other components of the dynamic pain connectome (default mode network [DMN], ascending and descending pathways) are abnormal in many chronic pain conditions. Here, we use resting-state functional magnetic resonance imaging and measures of static and dynamic functional connectivity (sFC and dFC), and regional BOLD variability to test the hypothesis that patients with MS have abnormal DMN-SN cross-network sFC, dFC abnormalities in SN-ascending and SN-descending pathways, and disrupted BOLD variability in the dynamic pain connectome that relates to pain inference and neuropathic pain (NP). Thirty-one patients with MS and 31 controls completed questionnaires to characterize pain and pain interference, and underwent a resting-state functional magnetic resonance imaging scan from which measures of sFC, dFC, and BOLD variability were compared. We found that (1) ∼50% of our patients had NP features, (2) abnormalities in SN-DMN sFC were driven by the mixed-neuropathic subgroup, (3) in patients with mixed NP, dFC measures showed that there was a striking change in how the SN was engaged with the ascending nociceptive pathway and descending modulation pathway, (4) BOLD variability was increased in the DMN, and (5) the degrees of sFC and BOLD variability abnormalities were related to pain interference. We propose that abnormal SN-DMN cross-network FC and temporal dynamics within and between regions of the dynamic pain connectome reflect MS pain features. Abstract : Supplemental Digital Content is Available in the Text.The brain networks related to salience and pain was disrupted in patients with multiple sclerosis pain, and related to pain interference and neuropathic pain features.